Hydration of Proton-conducting BaCe0.9Y0.1O3−δ by Decoupled Mass Transport - Dae-Kwang Lim (Nature Portfolio, 2017)
Abstract Mass relaxation profile of a perovskite-type oxide, BaCe0.9Y0.1O3−δ, was studied to understand decoupled diffusion of oxygen and hydrogen species during hydration/dehydration. The mass relaxation measurements are performed by thermogravimetric analysis (TGA) under various humidity conditions (Dry, −3.0 ≤ log(pH2O/atm) ≤ −1.6) at a constant oxygen partial pressure (log(pO2/atm) = −1.00 ± 0.01). The decoupled ions participated in hydration/dehydration reactions were proven to be at different ratios from the result introduced by the 8R m function. The enthalpy and entropy of non-stoichiometric hydration reaction, which considers each ratio of charge-carrier species, were −144.7 ± 3.7 kJ/mol and −147.8 ± 3.2 J/mol · K, respectively.